Immediate Impact of Vocal Demand, Likelihood of Dysphonia, and Performance Aspects in Amateur Protestant Singers - Santos, João Ricardo Ferreira; Depolli, Gabriel Trevizani [UNESP]; Azevedo, Elma Heitmann Mares; Moreti, Felipe [UNESP]; Guimarães, Michelle Ferreira (Elsevier, 2024)
Objectives: To analyze the immediate impact of vocal demand, probability of dysphonia, and performance aspects in amateur protestant singers. Methods: Cross-sectional, analytical study, with 76 amateur singers from a protestant church, 60 women and 16 men. All participants responded to a sociodemographic and performance questionnaire, the Evaluation of the Ability to Sing Easily for Brazil (EASE-BR), and the Dysphonia Screening Tool (DST-Br). The data were analyzed descriptively and inferentially, considering a significance level of 5%. Results: The singers reported good voice status after a performance, with the possibility of singing again if necessary. Most individuals had a low probability of dysphonia, showing a lower mean score compared to those with a moderate probability. There was an association between “trying to sing louder than others” and “vocal self-assessment” with the immediate impact of vocal demand and dysphonia screening. Implementing vocal rest was significantly associated with EASE-BR, and trying to sing louder than the instruments and being able to hear yourself well while singing and water intake were associated with the total DST-Br score. Conclusions: The immediate impact of vocal demand after performance on this population did not compromise their ability to sing easily. Most singers had a low probability of dysphonia. “Trying to sing louder than the instruments” and “ability to hear oneself well while singing and water intake” were associated with dysphonia screening.
Keywords: Dysphonia; Singing; Speech-Language and Hearing Sciences; Voice